An investigation of conventional machine learning approaches vs deep learning approaches in manufacturing context : bearing fault detection - Loy, Chee Wah (Nanyang Technological University, 2020)
In the realisation that ball bearing fault is the number one fault that most commonly occur in industrial applications and the potential hazard that it can bring, this paper aims to tackle the problem of bearing fault detection.